Structural plasticity of the nuclear envelope and the endoplasmic reticulum - Sheval, E.V.; Musinova, Y.R. (Вiopolymers and Cell, 2014)
The nuclear envelope is a double membrane structure, continuous with endoplasmic reticulum, and the morphological organization of both these structures is quite conservative. However, nuclear envelope and endoplasmic reticulum demonstrate distinct structural plasticity, i. e., based on common organization, cells may form various non-canonical membrane structures that are observed only in specialized types of cells or appear in different pathologies. In this review, we will discuss the mechanisms of the biogenesis of such non-canonical structures, and the possible role of this plasticity in the development of pathological processes. Ядерна оболонка – двомембранна структура, неперервна з ендоплазматичним ретикулумом, причому морфологічна організація цих структур досить консервативна. Однак для ядерної оболонки і ендоплазматичного ретикулуму характерна виражена структурна пластичність, тобто на основі спільної організації в клітинах можуть формуватися різні неканонічні структури, які виявляються або в спеціалізованих клітинах, або за розвитку деяких патологій. У представленому огляді розглянуто механізми біогенезу подібних неканонічних структур, а також можливу роль структурної пластичності у розвитку патологічних процесів. Ядерная оболочка – двухмембранная структура, непрерывная с эндоплазматическим ретикулумом, причем морфологическая организация этих структур достаточно консервативна. Однако для ядерной оболочки и эндоплазматического ретикулума характерна выраженная структурная пластичность, т. е. на основе общей организации в клетках могут формироваться различные неканонические структуры, выявляющиеся либо в специализированных клетках, либо при развитии некоторых патологий. В настоящем обзоре рассмотрены механизмы биогенеза подобных неканонических структур, а также возможная роль структурной пластичности в развитии патологических процессов.